Autosomal recessive IL12RB1 mutation: A case report of a Sudanese child and his father - Abdelmajeed, Omaima; Ali, Muna Mohammed Dawoud; Erwa, Nahla Hashim; Mustafa, Alamin; Ahmed, Yassin Abdelraheem; Ahmed, Rogaia Hasap Alrasoul; Mohammed, Hala Hamza Eltayeb; Hassan, Malaz Elsadeg; Ahmed, Monzir; Algam, Shima (Frontiers in Immunology, 2023)
Introduction: Mendelian susceptibility to mycobacterial disease (MSMD) is a rare inherited condition characterized by selective susceptibility to weakly virulent mycobacteria, such as substrains of the Bacille Calmette-Guérin (BCG) vaccine and different environmental mycobacteria. Case presentation: A seven-year-old Sudanese boy was referred to the immunology clinic with a suspected diagnosis of MSMD. This followed multiple presentations with disseminated tuberculosis and Typhoid fever. Genetic testing surprisingly revealed two pathogenic homozygous variants in IL12RB1 Exon 9, c.913A>T (p. Lys305*) in both the patient and his father, with completely healthy a symptomatic, carrier mother who is not blood related to the father. Conclusions: It is challenging to diagnose MSMD, especially in developing countries where health systems are poor and have limited resources. Family history and genetic tests may help in early MSMD treatment and avoiding disease complications. Keywords: Immunology, Bacille Calmette-Guérin (BCG) vaccine, Mendelian Susceptibility to Mycobacterial Diseases, Tuberculosis, and IL12RB1 mutation.